Quantifying Innovation Potential: An Index System and Model for China’s High-Tech Industry Development Zone - Su, Chenqing; Inthawongse, Choat; Amdee, Noppadol (วารสารวิชาการเทคโนโลยีอุตสาหกรรม : มหาวิทยาลัยราชภัฏสวนสุนันทา, 2024)
The aim of this study is to investigate the innovative capacity of high-tech zones in China. To this end, we have developed an evaluation index system and established a solid theoretical basis for it. Our evaluation system includes four first-level indicators, eight second-level indicators and 28 third-level indicators, whose weights were determined using the entropy weight method. In addition, we applied the catastrophe progression method to comprehensively assess the innovative capacity of high-tech zones, capture innovation dynamics and identify areas for improvement. The novelty of this study lies in the construction of a multi-level index system based on the framework of cybernetics and information theory. By combining the entropy weighting method and the catastrophe progression method, we provide for the first time a scientific and comprehensive method for assessing innovation capability. Our research not only reveals the strengths and weaknesses of the innovation capability of high-tech zones, but also provides practical assessment tools and theoretical support for their further development. The results show that the systematic index system and scientific assessment methods can effectively evaluate the innovation capability of high-tech zones and provide deep insights and suggestions for improvement. Overall, our study provides valuable insights and practical guidance for the continuous innovation and development of high-tech zones in China.